Social Networking and Transnational Capitalism - David Kreps (tripleC: Communication, Capitalism & Critique)
Social Networking Sites (SNS) have become a key component of users’ experience of the internet.  Whilst much has been made of the social dynamics of online SNS, the influence of the structures and operations of these sites – and the business models behind them - on users is rarely accounted for.  This paper argues that behind the social behaviours supported by SNS, there is a growing shift towards viewing online communities as commodities, and SNS as an extension of mainstream capitalist ideologies fostered by existing patterns of commercialization and consumption. Using the works of Gramsci, Gill and Hardt & Negri to provide a critical grounding, this paper explores the popular SNS site ‘Facebook’ and suggests that SNS may feel to the users to be free, social, personal, but in fact SNS are business as usual.